Wear resistance enhancement of HVOF-sprayed WC-Co coating by complete densification of starting powder. (June 2020) - Wang, Haibin; Qiu, Qingfan; Gee, Mark; Hou, Chao; Liu, Xuemei; Song, Xiaoyan
Abstract: A novel alumina-assisted treatment process was proposed to manufacture fully densified and perfectly spherical WC-Co particles for thermal spraying applications. In as-sprayed coating, the decarburization phenomenon common in previous studies was almost entirely eliminated, and a unique binder structure with nanocrystalline and amorphous Co co-existing was obtained. Owing to the strengthening effects of nanocrystalline Co and WC/Co interfacial bonding, the wear resistance of the new coating was 4 times higher than that of the conventional coating prepared with a porous feedstock. Instead of plastic deformation, interface fracture and micro-cutting that mainly occurred in conventional WC-based coatings, fracture of WC grains and subsequent oxidation dominated wear failure of the new WC-Co coating. The present work opens up new opportunities for the fabrication of dense ceramic-metal composite particles and wear-resistance enhancement of cermet coatings. Graphical abstract: Unlabelled Image Highlights: Decarburization common in HVOF-sprayed WC-Co coatings was entirely eliminated by complete densification of starting powder. The prepared coating has a unique microstructure with coexisting amorphous and nanocrystalline Co. Wear resistance of the present coating was remarkably improved by 4 times compared to that of the conventional counterpart. WC fracture and oxidation were dominant wear mechanisms of the new coating instead of deformation and micro-cutting.